Intérêt du principe de solidarité écologique pour la valorisation des usages pastoraux dans les Pyrénées - Sigrid Aubert (VertigO)
Some French lawyers support the establishment of a new category of goods, the “common goods” to deal with the ecological emergency. The political anthropology of juridicity focuses its attention on the social dynamics associated with "commoning". The aim is to restore the dynamics of law revealed by legal pluralism by paying particular attention to the conditions of emergence and promotion of social innovations carried by collectives of users of the land and the natural resources. In many situations, these social innovations contribute to the assumption of responsibility by citizens for interdependent relationships between humans and between humans and non-humans, in contexts where the proposals put forward by the State or the markets do not seem satisfactory to the inhabitants of the territories concerned. According to this approach, it is possible to postulate that the general principle of ecological solidarity is completed by a legal fact: the existence of a (social and) ecological solidarity experienced by a collective of users (human and non-human). This fact generates, between the members of the communities of uses considered, duties and prerogatives, likely to constitute the source of a right opposable to third parties: a right to the use of the land and the natural resources it bears. The customary law associated with the expression of ecological solidarity can thus lead to the reification of particular, existing or desirable behaviours (including behaviours associated with the exercise of public power) at different territorial scales.